1963
DOI: 10.1149/1.2425860
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Electrodeposition from Aqueous Solutions of Square Planar Complexes

Abstract: Cathode current efficiencies and/or cathode potentials have been measured for a variety of spin-paired square planar complexes of Pt(II), Pd(II), and Au(III) in aqueous solutions. It was found that the tendency toward electrodeposition depends on the bond strengths of the particular ligands about the central metal ion, and that the over-all charge of the complex influences current efficiency in the expected direction, i.e., complexes with more negative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1964
1964
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In addition, a previous paper showed that the mechanism of deposition of this complex did not involve previous dissociation. 32 In short, there is evidence for the surface catalytic activity of electrodeposited Pd black (see Fig. 2).…”
Section: Effect Of the Meoh Concentration-inmentioning
confidence: 97%
“…In addition, a previous paper showed that the mechanism of deposition of this complex did not involve previous dissociation. 32 In short, there is evidence for the surface catalytic activity of electrodeposited Pd black (see Fig. 2).…”
Section: Effect Of the Meoh Concentration-inmentioning
confidence: 97%
“…Other stripping solutions tried were KCN, KCN-NaOH mixtures, NaN02, NH3-NaCl mixtures, NH3-NaOH mixtures, KSCN, HI, KBr, NaOH, and K2S03. They were selected according to the platinum bond strength of the anion (32)(33)(34). None of these solutions showed any indication of platinum dissolution.…”
Section: Methodsmentioning
confidence: 99%